Nutritional support for oral cancer patients: What every nurses should know? - Ribwar Arsalan Mohammed; Sirwan Khalid Ahmed (Oral Oncology Reports)
This paper discusses the important role of nutritional support in nursing care for patients with oral cancer, a condition that is becoming more common worldwide. Unfortunately, malnutrition often goes unnoticed, making treatment complications worse and reducing survival rates. By working together and using evidence-based practices, nurses can address these challenges by providing personalized nutritional interventions for each patient. Regular nutritional assessments, comprehensive care plans, and patient education are crucial parts of this approach, helping patients manage treatment side effects and achieve better results. However, nurses face obstacles like ethical dilemmas, limited resources, and healthcare disparities. This highlights the need for continuous education and advocacy to improve care and enhance the well-being of people diagnosed with oral cancer.